PENGUKURAN DAN ANALISIS PEMIMPIN BERBASIS NILAI-NILAI BUDAYA ORGANISASI LOKAL - Daryono Daryono; Syaiful Bakhri (Jurnal Akuntansi & Bisnis, 2018)
The diversity of local culture in Indonesia is priceless wealth. One culture that is owned by Indonesia has become the basis for most of the behavior that exists in an organization. Individual, group, and organizational behavior can’t resist the influence of local culture. At present there are many theories and sciences especially in the field of organizational behavior based on the results of studies from abroad which adopt values originating from the region. One of the individual behaviors that has developed a lot now is about the theory of leadership. Seeing these developments, it is necessary to develop a new model that explains how and what kind of leadership is around us.This research is expected to develop a model of leader behavior based on the surrounding culture. Many theories of organizational behavior that discuss the behavior of leaders who develop strongly today are a reflection of foreign culture that is actually also contained in our cultural values. Therefore this study will answer and explain these problems. The hope in the future is an organization theory will be realized, especially regarding leadership theory that is stronger because it complements the existing theories, and theories that can be applied by local communities because they are a reflection of their own culture. Explore the values, concepts and constructs that develop around to then be harmonized with the theory that originally existed. The method that can be used is through an in-depth exploration process to then be confirmed by a theory that previously existed. The first step of course can be achieved by conducting a group discussion group to explore the values, concepts and constructs of organizational behavior, then analyzing the factors to confirm, then harmonizing with the existing theories first. Key words: Leader, Behavior, Values, Culture.